2003
DOI: 10.1029/2002je001869
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and time domain permittivity measurements on solid CO2 and solid CO2–soil mixtures as Martian soil simulants

Abstract: [1] Permittivity and conductivity measurements were performed to assess the dielectric behavior of solid CO 2 (i.e., CO 2 ice, snow, and powder) and solid CO 2 /soil mixtures. For comparison, some dielectric measurements were also conducted on H 2 O ice, dry glass beads, glass beads saturated with water, drained glass beads, and frozen drained glass beads. The measurements were performed in the frequency domain (20 Hz to 1 MHz) using a capacitive cell (Parallel Plate Capacitor) and in the time domain using a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…The low values of the real part of permittivity measured for CO 2 powder (and CO 2 snow) were confirmed by TDR measurements, as shown in Table . This table compares the values found by Pettinelli et al [] with those reported in Simpson et al [], who measured samples of CO 2 powder as a function of density within the microwave frequency range of 2.2–12 GHz. Taking into account the difference in sample densities, the agreement between the two sets of measurements is significant, also in the case of the solid CO 2 ice sample, which was measured in Pettinelli et al [] and estimated using the Maxwell‐Garnett mixing formula in Simpson et al [].…”
Section: Dielectric Properties Of Nonwater Icessupporting
confidence: 65%
“…The low values of the real part of permittivity measured for CO 2 powder (and CO 2 snow) were confirmed by TDR measurements, as shown in Table . This table compares the values found by Pettinelli et al [] with those reported in Simpson et al [], who measured samples of CO 2 powder as a function of density within the microwave frequency range of 2.2–12 GHz. Taking into account the difference in sample densities, the agreement between the two sets of measurements is significant, also in the case of the solid CO 2 ice sample, which was measured in Pettinelli et al [] and estimated using the Maxwell‐Garnett mixing formula in Simpson et al [].…”
Section: Dielectric Properties Of Nonwater Icessupporting
confidence: 65%
“…The model background is described by σ = 10 −10 S/m and ε r = 4 and the layer by σ = 10 −6 S/m and ε r = 7, a setup typical for cold ice-dust mixtures with intervening water ice sheets. The chosen dielectric properties are consistent with those determined from laboratory experiments conducted at various temperatures and frequencies using mixtures of H 2 O and CO 2 ice with soil (Pettinelli et al 2003) and dry powders of dunite, montmorillonite, and kaolinite (Herique et al 2002). Such granular dust particles are considered as best available analog material for the refractory component of comets in terms of composition and grain size distribution.…”
Section: Model Geometrysupporting
confidence: 64%
“…The electrical conductivity of terrestrial rocks and sediments in the presence of moisture is about 10 mS/m (Grard 1990) and range from 10 −9 to 10 −10 S/m for dry lunar-type regolith at a frequency of 1 kHz (Carrier et al 1991). Thus, dielectric losses are negligible, even at the highest frequency, and the dielectric constant certainly dominates permittivity measurements in dry, porous regolith (Martinez and Byrnes 2001;Pettinelli et al 2003). …”
Section: Measurement Principlementioning
confidence: 99%
“…The constant value of 3.15 + i 6.3 × 10 −4 , as in the work by Picardi et al [2004], is a good representation for temperatures between 200 K and 230 K with respect to the models. Pettinelli et al [2003] experimentally obtained a range of 2.89 ≤ ɛ′ ice ≤ 3.29 and ɛ″ ice ∼ 6 × 10 −2 for 1 MHz and 250 K, depending on the method used. Here we adopt the same value as Picardi et al [2004], which is not only in agreement with the values discussed above, but also is consistent with the observations of a low‐loss, nearly pure ice northern polar layered deposits by both Picardi et al [2005] and Phillips et al [2008].…”
Section: Observationsmentioning
confidence: 98%